Laser cooling of relativistic heavy-ion beams for FAIR. (26th November 2015) - Winters, D; Beck, T; Birkl, G; Dimopoulou, C; Hannen, V; Kühl, Th; Lochmann, M; Loeser, M; Ma, X; Nolden, F; Nörtershäuser, W; Rein, B; et al.
Abstract: Laser cooling is a powerful technique to reduce the longitudinal momentum spread of stored relativistic ion beams. Based on successful experiments at the experimental storage ring at GSI in Darmstadt, of which we show some important results in this paper, we present our plans for laser cooling of relativistic ion beams in the future heavy-ion synchrotron SIS100 at the Facility for Antiproton and Ion Research in Darmstadt.